Sophie Horan: capstone - Horan, Sophie, artist (Colorado State University. Libraries, 2025)
The artist's statement: I am a determined artist who is experienced with digital media such as the Adobe suite, though I also excel in traditional mediums. Collage, oil and acrylic paint, watercolors, inks, and photography are all part of my repertoire, though I love working with new and unconventional mediums. I love using both traditional and digital mediums to design, as both have distinct feels to them. I can make both two and three dimensional items, and I am always excited to start new projects. While working with clients, I communicate any ideas I have and regularly work with them to keep projects on track. I also iterate illustrations and designs while experimenting to emphasize any aspects the client wants. The process of developing any project is very rigorous and variable, but I am reliable and flexible enough to meet any expectations. While designing this book, for example, I changed colors, sketched out and used multiple rough drafts to organize the book, and made time to print out the book both as a spread and as a functional book. I am inspired by the natural world and the many processes that exist within it. From decay and growth, to movement and stagnation, to light and lack thereof, I dive into the rules that bind them and how they work. Themes of empathy and understanding are other aspects I aim to incorporate. Though the world is often cold and unforgiving, I want to emphasise that understanding people are still around, and being one is rewarding.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design